REDUPLIKASI DALAM KUMPULAN CERPEN TAWA GADIS PADANG SAMPAH KARYA AHMAD TOHARI - Apriangga, Wan; Salem, Laurensius; Patriantoro, Patriantoro (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThis research is a study that focuses on discussion about reduplication in a collection of short stories Tawa Gadis Padang Sampah by Ahmad Tohari. The reuplication is a classified reduplication based on the form, meaning and semantic function which is in the use of language in a collection of short stories Tawa Gadis Padang Sampah by Ahmad Tohari. The type of form(59) reduplication, meaning and semantic function became the main discussion in this research, which classified based on formulation of existing problems. Based on the result of the study that has been conducted, found a kind of form, meaning, and semantic role in A Collection of Short Stories Tawa Gadis Padang Sampah by Ahmad Tohari. The form of reduplication in this research found four types of reduplication form amounting 139 from 179 data which has been collected. The meaning of reduplication in this research founds 8 types of meaning in 139 reduplication data. Semantic reduplication role in this research founds four types of function which could be analyzed based on the theory. The result of this research can be used in language text exposision structure leaning in the school. Keywords: Reduplication. Short Stories